Strategic use of honey bees (Apis mellifera L.) to increase the number and size of fruits in kiwifruit (Actinidia chinensis var. deliciosa) - David, Maria Angela; Sanchez, Enrique Eduardo; Martinez, Analia Noelia; Murillo, Natalia Lorena; Marcellán, Olga; Atela, Osvaldo; Palacio, María Alejandra (Elsevier, 2022)
Fruit size in kiwifruit depends mainly on the number of seeds or fertilized ovules. Pollination by wind is not enough to obtain a fruit size accepted by the market, so it is necessary to perform this practice by means of bees and/or artificially. Since there are controversies regarding the efficiency of each practice, the objective of this study was to determine the effect of pollination with honey bees, artificial-hand pollination and the combination of both methods, on fruit set at harvest, fruit size (length, minor and major diameter, weight), number of seeds, maturity and internal quality indexes (color, firmness, soluble solids content, dry matter, titratable acidity). The trial took place in the 2018/2019 and 2019/2020 seasons on a ‘Hayward’ kiwifruit orchard located in Miramar, in the southeast of Buenos Aires Province, Argentina. Treatments were applied in three uniform canes on 9 vines. Honey bee and combined pollination treatments showed a better fruit set at harvest (24.6% and 18.5% higher, respectively) compared to artificial-hand pollination. Also, the fruits originated from honey bee pollinated flowers and the combined treatment had higher length (4.8% and 5.4%), major diameter (5.5% and 5.7%), minor diameter (2.9% and 3.5%), weight (14.6% and 15.3%) and number of seeds (11.6% and 10.4%) with respect to those obtained by artificial-hand pollination. No significant differences were detected between treatments for maturity/quality indexes at harvest. Pollination with honey bees and the combined method were the most efficient. These results indicate that proper management of honey bees for kiwifruit pollination improves yield without affecting maturity, and preserving fruit quality indexes.